Surgical anatomy of the internal thoracic arteries and their branching pattern: a cadaveric study - Paliouras, Dimitrios (Ann Transl Med, 2015)
BACKGROUND: The purpose of this study is to review the anatomic characteristics of internal thoracic artery (ITA) and its branches, in order to pursue the extension of its utilization and avoid intraoperative and postoperative complications. METHODS: The study was carried out on anterior chest walls obtained during routine autopsies of 50 specimens (30 male, 20 female). Macroscopic and microscopic dissection was performed and the following were studied: origin, length and termination of ITA, size and distance from the sternum, and types of branches. RESULTS: From the origin to the termination point, the length of the left internal thoracic artery (LITA) varied from 159 to 220 mm; with a mean of 182.60 mm. The length of the right internal thoracic artery (RITA) varied from 150 to 231 mm; with a mean of 185 mm. Four types of branches were distinguished. The RITA mean diameter was 2.31 mm, measured at the 2(nd) intercostal space, while the distance from the sternum was 12.77 mm, measured at the 3(rd) intercostal space. The LITA mean diameter was 1.98 mm with the distance from the sternum measured at 12.01 mm. CONCLUSIONS: ITA has become the primary conduit for cardiac bypass surgery; many studies have generated fundamental anatomical knowledge for its clinical utilization, which is always useful in order to avoid intraoperative and postoperative complications.